Corporate Social Responsibility Disclosure and Firm Performance of Malaysian Public Listed Firms - Mohd Waliuddin, Mohd Razali1; Hii, Winnie Sin Sin; Janifer, Lunyai; Yau, Josephine Tan Hwang; Irma Yazreen, Md Yusoff (Canadian Center of Science and Education, 2018)
Corporate Social Responsibility (CSR) disclosure has become a rising concern for the public listed firms worldwide due to its ability to enhance firm’s market performance and financial performance. The main objective of this study is to investigate the relationship between CSR disclosure and firm performance of Bursa Malaysia’s listed companies based on their market value added (MVA), return on equity (ROE) and return on assets (ROA). 324 samples of public listed companies’ annual report for the period of 2014 to 2016 were obtained from Bursa Malaysia and examined. The extent of their CSR disclosure were measured and analyzed. After accounting for control variables such as firm size, firm age, firm leverage and firm liquidity, the result shows that there is a positive significant relationship between CSR disclosure and firm performance in terms of ROA and ROE. This reveals that high level of CSR disclosure helps firms to achieve optimum performance through increased competitiveness, improved firm’s image amongst society, and creates new opportunities in the marketplace. The findings also showed mix results among the control variables towards firm performance. For future research, this paper recommends to extend the study by using different CSR disclosure measurement, different firm performance measurement such as return on investments (ROI) and Tobin’s Q and different samples.